2011
DOI: 10.1002/elps.201100128
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that SNPs in the high mobility group‐A2 gene (HMGA2) are associated with adult height in the Japanese population; wide‐ranging population survey of height‐related SNPs in HMGA2

Abstract: Adult height is a highly heritable trait in that multiple genes are involved. Recent genome-wide association studies have identified a novel single-nucleotide polymorphism (SNP) rs1042725 in the high mobility group-A2 gene (HMGA2) and shown it to be associated with human height in Caucasian populations. We performed a replication study to examine the associations between SNPs in HMGA2 and adult height in the Japanese population based on autopsy cases. Although we could not confirm a significant association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The most important factor is GH. After liver GH binds to GH, IGF-1 is secreted, and IGF-1 inhibits GH secretion by negative feedback (18). The IGFBP-3 gene is located in the 7p12-p13 region and is highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor is GH. After liver GH binds to GH, IGF-1 is secreted, and IGF-1 inhibits GH secretion by negative feedback (18). The IGFBP-3 gene is located in the 7p12-p13 region and is highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is mainly synthesized and secreted by the liver, and its expression varies under the influence of various factors, including GH. GH has a direct effect on target cells, stimulating the synthesis and secretion of IGF-1, and inhibiting the secretion of GH through negative feedback (11,12).…”
Section: Discussionmentioning
confidence: 99%
“… 38 Further, HMGA2 rs7968902 is significantly correlated with the height of the Japanese population. 39 We previously explored the effect of HMGA2 SNPs on susceptibility to different diseases and found that HMGA2 polymorphisms weakly influence Wilms tumor. 40 In addition, the HMGA2 SNPs, rs8756A>C and rs968697T>C, are associated with lower susceptibility to neuroblastoma 41 and hepatoblastoma, 42 respectively.…”
Section: Discussionmentioning
confidence: 99%